Effect of sorghum (Sorghum bicolor L.) on metabolic variables in adults - Anunciação, Pamella Cristine (2017)
Sorghum presents as a possibility of consumption to conventional cereals because it is an excellent source of bioactive compounds, which contribute to its high antioxidant capacity. Sorghum-based products can therefore be useful in reducing the risk of chronic noncommunicable diseases. This study aimed to evaluate the effect of the consumption of extruded sorghum-based preparations on the metabolic variables in adult subjects. To evaluate the effect of extruded sorghum consumption on the glycemic response of a subsequent meal (Article 1), 10 eutrophic and normoglycemic adults participated in 4 experimental sessions in which one of the 3 drinks containing different sorghum genotypes or a non-sorghum drink were consumed (control). Drinks were prepared by homogenizing the ingredients (sorghum flour, milk powder, cocoa powder, and sweetener) in 200 ml of mineral water. Thirty minutes after ingestion of one drink (all containing 25g of available carbohydrate) volunteers consumed a glucose solution. The glycemic response was monitored at times 0 (before glucose solution intake), 15, 30, 45, 60, 90 and 120 minutes (after consumption of the glucose solution). Results showed that ingestion of the P 3DXA drink (containing proanthocyanidins and 3- deoxyanthocyanidins) resulted in lower postprandial iAUC than the other sorghum containing drinks. Sorghum-containing drinks minimized the postprandial blood glucose peak compared to non-sorghum drink. Sorghum and wheat-based preparations (breakfast cereal and drinks) were developed for volunteers consumption in the intervention study (Article 2). These preparations were evaluated for sensory acceptance, occurrence and concentration of bioactive compounds (3-deoxyanthocyanidins, flavones, flavanones, total phenolics and vitamin E) and antioxidant capacity. Sorghum breakfast cereal was more widely accepted than whole wheat cereal. The sorghum cereal presented higher content of 3-deoxyanthocyanidins (100% higher), total phenolic compounds (98.2% higher) and antioxidant capacity (87.9% higher) than wheat breakfast cereal. Flavones and flavanones were not detected in both cereals. Vitamin E content was 78.6% higher in whole-wheat breakfast cereal. To evaluate the effect of the consumption of sorghum- based preparations in the control of metabolic variables (Article 3), 24 overweight men participated in the study. The randomized crossover study consisted of 2 periods of 8 weeks with at least 4 weeks of washout, in which volunteers were allocated in 2 treatments: consumption of sorghum or wheat-based preparations. Body composition, lipid and glycemic profile, insulin resistance, oxidative stress markers, serum vitamins and carotenoids, and caloric and macronutrient intake were evaluated at the beginning and at the end of each intervention period. The consumption of extruded sorghum for eight weeks led to a reduction in body weight, waist circumference, percentage of body fat and increased levels of glutathione peroxidase. To evaluate the effect of sorghum consumption on the composition of the intestinal microbiota, during the second stage of the intervention study, at the beginning and at the end of 8 weeks, a stool sample was collected from 22 participants and a blood sample was collected by venipuncture to determine the markers of inflammatory response. Stool samples were collected in sterile vials, kept under refrigeration and delivered in a maximum of 12 hours. Aliquots were stored at -80°C until analysis. The fecal hydrogen potential (pH) was measured in digital pHmeter immediately after sample preparation. Organic acids were determined by high performance liquid chromatography with refractive index detection. The composition of the intestinal microbiota was determined by PCR with the purpose of characterizing Proteobacteria, Firmicutes and Bacteroidetes. Inflammatory markers were analyzed by ELISA using specific kit ((HCYTOMAG-code 60K, Millipore). The consumption of extruded wheat reduced waist circumference, but increased fasting blood glucose. After 8 weeks of intervention, there was no change in faecal pH, organic acid concentration and microbiota composition in both groups. There was also no change in the inflammatory markers evaluated. It is suggested that the ingestion of sorghum-based preparations may be an effective measure to reduce postprandial blood glucose from the subsequent meal, improve glycemic control, assist in weight reduction, and improve oxidative stress. Consumption of whole grain sorghum-based cereals should be encouraged as it has good sensory acceptance and is a source of bioactive compounds that promote human health benefits. Further studies on the effect of sorghum consumption on the composition of the intestinal microbiota should be performed with a larger sample size or using more specific techniques.